2008
DOI: 10.1097/jgp.0b013e318187ddd3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use Among Older African Americans: The National Survey of American Life

Abstract: Objectives The objective of this study was to examine mental health services utilization of older African Americans using data from the National Survey of American Life (NSAL). Methods A sub-sample of African American respondents aged 55 years or older (n=837) was used for this study. Thirteen mental disorders, including mood, anxiety, and substance disorders, were assessed using the Diagnostic Statistical Manual-IV World Mental Health Composite International Diagnostic Interview. Seventy-four respondents (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 30 publications
(36 reference statements)
5
47
4
Order By: Relevance
“…The covariates of service use were not surprising, again extending prior studies and consistent with the NEM (10), with key demographic (age), need (major depressive episode diagnosis), attitudes (intention), prior experience (antidepressant use), and social context (advice) as important factors (19, 4951). Stigma was not associated with service use, which could be due to its measurement, statistical power, the possibility that stigma was not as salient for this sample as it would be for a more severely depressed sample (25), or the possibility that stigma is not as significant a barrier as previously thought (52).…”
Section: Discussionsupporting
confidence: 76%
“…The covariates of service use were not surprising, again extending prior studies and consistent with the NEM (10), with key demographic (age), need (major depressive episode diagnosis), attitudes (intention), prior experience (antidepressant use), and social context (advice) as important factors (19, 4951). Stigma was not associated with service use, which could be due to its measurement, statistical power, the possibility that stigma was not as salient for this sample as it would be for a more severely depressed sample (25), or the possibility that stigma is not as significant a barrier as previously thought (52).…”
Section: Discussionsupporting
confidence: 76%
“…The covariates of service use were not surprising, again extending prior studies and consistent with the NEM (10), with key demographic (age), need (major depressive episode diagnosis), attitudes (intention), prior experience (antidepressant use), and social context (advice) as important factors (19, 4951). Stigma was not associated with service use, which could be due to its measurement, statistical power, the possibility that stigma was not as salient for this sample as it would be for a more severely depressed sample (25), or the possibility that stigma is not as significant a barrier as previously thought (52).…”
Section: Discussionsupporting
confidence: 76%
“…Approximately two thirds of the suicide attempters in our study report seeking treatment for their emotional problems in the general medical sector, which is common among the elderly that engage in suicidal behavior (Cohen et al, 2008). In fact, Neighbors and colleagues found that older Black Americans tend to seek mental health care in the general medical sector more than the mental health sector (Neighbors et al, 2008).…”
mentioning
confidence: 65%